Ukrainian Pianist Oleksandr Kozarenko - Komenda, Olha I.; Odarchuk, Nataliia A.; Коменда, Ольга Іванівна; Одарчук, Наталія Андріївна (My University, 2016)
The article is devoted to the creative personality of the modern Ukrainian pianist Oleksandr Kozarenko. It discloses the environment and conditions of shaping the musician, the priorities of his concert as well as contest activity, repertoire peculiarities, methodic and artistic principles of performing style. The article applies the scientific approaches, developed by the Kyiv School’s musicologists (Yuri Chekan, Olena Zin’kevych, Valentyna Redia and others), and connected with working out the issues of creative individual’s psychology, intonational nature of music art, genre-style analysis, music speech and interpretation. The suggested opinions are the results of continual observation of Oleksandr Kozarenko’s activity, a face-to-face communication with the pianist; they are based on the artistic-performing as well as interpretational analysis of his numerous solo and ensemble performances. Some statements are confirmed by the pianist’s utterances recorded during a face-to-face communication. Positioning O. Kozarenko as a representative of the Ukrainian piano school (he is a Kyiv Conservatoire graduate, Vsevolod Vorobyov’s class), his deep interest in the Ukrainian repertoire, particularly the works by Mykola Lysenko, the founder of the Ukrainian composer school, professing the principles of melodious pianism as the key idea of the national performing style form the background of the made conclusions.
Keywords: pianism; performing style; theatrical performance; performing genre tendency; melodic texture